Longstanding Persistent Atrial Fibrillation Ablation: How Do You Perform It? - Gianni, Carola; Natale, Andrea; Al-Ahmad, Amin (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Longstanding-persistent atrial fibrillation is one of the most challenging arrhythmias to treat. While radiofrequency catheter ablation is highly effective in paroxysmal atrial fibrillation, pulmonary vein antral isolation (including posterior wall isolation) alone is not enough for nonparoxysmal atrial fibrillation, other targets should be sought in this population. In this case report, we will describe our approach in a typical patient presenting for a first-time ablation procedure for longstanding persistent atrial fibrillation.